Heat-conducting anti-puncture silica gel material for explosion-proof lithium battery and preparation method thereof
By using polydopamine derivatives in thermally conductive silicone materials to modify boron nitride and modify silver nanoparticles, modified boron nitride is obtained as a thermal filler, which solves the problems of low thermal conductivity and complex preparation of existing thermally conductive silicone materials, and achieves the improvement of high thermal conductivity and strength.
Patent Information
- Application Number
- CN202510588546.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-06-27
AI Technical Summary
The existing thermal conductivity of the thermal conductivity of the silicone materials is relatively low, the preparation is complicated, and the amount of thermal conductivity is added too much, which affects the mechanical strength.
The surface of boron nitride is modified in an oily organic solvent and silver nanoparticles are modified on boron nitride to obtain modified boron nitride as a thermal filler and added to the silicone material.
The thermal conductivity and strength of the silicone material are significantly improved, the preparation process is simplified, the amount of thermally conductive filler is added, and the mechanical properties are maintained.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal conductive silicone materials, and particularly relates to a thermal conductive and puncture-proof silicone material for explosion-proof lithium batteries and a preparation method thereof. Background Art
[0002] With the rapid development of new energy vehicles, people's consumption demand for new energy vehicles is also increasing. When a new energy vehicle is running, the power battery pack provides running power for the new energy vehicle by continuously discharging, generating a certain amount of heat, which causes the temperature of the power battery pack to rise. The heat generated by the power battery pack accumulates over a long period, affecting the service life of the battery. Therefore, a thermal conductive silicone sheet is needed to dissipate heat from the power battery pack. Due to the inherent excellent high and low temperature resistance, high elasticity, chemical inertness, and excellent electrical insulation of silicone, it has been applied to the thermal conductive and insulating composite materials of new energy vehicles. However, the thermal conductivity of silicone is relatively low, only about 0.2 W / (m·k). Therefore, the preparation of a high thermal conductive silicone composite material with electrical insulation is becoming the research focus in the field of heat dissipation.
[0003] Meanwhile, in order to improve the performance of silicone in new energy battery packs, silicone is often combined with other functional layers. For example, CN115286832A discloses a thermal conductive silicone sheet for new energy vehicles and a preparation method thereof. The silicone sheet includes a polyimide film and a thermal conductive silicone layer attached to the surface of the polyimide film. The polyimide film includes: pyromellitic dianhydride 30 - 40%, diaminodiphenyl ether 20 - 30%, thermal conductive filler 10 - 17%, modifier 5 - 10%, solvent 10 - 20%, end-capping agent 2 - 5%; the thermal conductive silicone includes: vinyl-terminated silicone oil 6 - 30%, hydrogen-containing silicone oil 3 - 16%, thermal conductive filler 50 - 90%, leveling agent 0.5 - 2.5%, vulcanizing agent 0.1 - 1%, catalyst 0.3 - 2.5%, inhibitor 0.05 - 0.3%; this thermal conductive silicone sheet has a heat dissipation, puncture-proof and protective effect on the new energy vehicle battery module. However, the preparation of this thermal conductive silicone sheet is relatively complex, and the addition amount of the thermal conductive filler exceeds 50%.
[0004] It is necessary to provide a silicone material with a low addition amount of thermal conductive filler that does not affect the mechanical strength, and a method with simple ingredients and preparation method. Summary of the Invention
[0005] In order to solve the technical problems existing in the prior art, the present invention provides a thermal conductive and puncture-proof silicone material for explosion-proof lithium batteries, which includes, by weight parts,
[0006] vinyl-terminated silicone oil 50 - 100 parts; hydrogen-containing silicone oil 30 - 60 parts; thermal conductive filler 2 - 20 parts; catalyst 0.5 - 1 part; inhibitor 0.2 - 0.5 part; leveling agent 0.5 - 2 parts;
[0007] The thermal conductive filler is at least one of aluminum nitride, silicon carbide, boron nitride or modified boron nitride.
[0008] The thermal conductivity of boron nitride can reach 250 - 300 W / (m·K), and its properties are stable. Although a relatively high thermal conductivity can be achieved by simply using boron nitride, the viscosity increases sharply after a large amount of filling (the addition amount is greater than 20 wt.%).
[0009] The thermal conductivity of aluminum nitride can reach 200 W / (m·K), but after absorbing moisture, it will react with water to generate aluminum hydroxide, which will interrupt the heat conduction path. Therefore, a silane coupling agent is often required for treatment during use.
[0010] Silicon carbide has a relatively high thermal conductivity. Due to the limitations of the preparation process, it is difficult to remove the carbon and graphite generated during the synthesis process, resulting in a low product purity, high conductivity, and being not suitable for electronic adhesives. In addition, its large density makes it easy to precipitate and stratify in silicone adhesives, affecting the product application. It is more suitable for epoxy adhesive matrices.
[0011] Furthermore, the preparation method of the modified boron nitride is as follows:
[0012] Disperse boron nitride and polydopamine derivatives in an oily organic solvent, react, and collect the insoluble matter.
[0013] Disperse the insoluble matter and the silane coupling agent in silver ammonia solution, and then add a reducing agent to react to obtain modified boron nitride.
[0014] Currently, many studies have dispersed some thermal conductive fillers in a weakly alkaline dopamine solution to generate polydopamine on the surface of the thermal conductive fillers for surface modification, improving their surface properties and enhancing their compatibility in silicone rubber. However, the preparation conditions are still relatively cumbersome, and it is difficult to control the polymerization conditions. Therefore, in the present invention, polydopamine derivatives are used to modify the surface of boron nitride in an oily organic solvent. The results show that the compatibility between boron nitride and silicone rubber is significantly improved, so that even when the addition amount of boron nitride is large, the viscosity will not increase significantly. In addition, the thermal conductivity of silver particles is also excellent, and silver particles are further modified on boron nitride.
[0015] Furthermore, the mass ratio of the boron nitride, polydopamine derivatives and oily organic solvent is 1 - 5:0.2 - 1:50 - 100.
[0016] The oily organic solvent is toluene or xylene.
[0017] Furthermore, the polydopamine derivative is hydroxy polyethylene glycol dopamine.
[0018] Furthermore, the mass ratio of the insoluble matter, silane coupling agent and silver ammonia solution is 1 - 5:0.1 - 0.5:20 - 50.
[0019] The silane coupling agent is at least one of KH550, KH550 or KH560.
[0020] Furthermore, the mass concentration of silver in the silver ammonia solution is 0.1-0.5%.
[0021] Furthermore, the mass ratio of the reducing agent to the insoluble matter is 0.05-0.2:1;
[0022] The reducing agent is at least one of glucose, ascorbic acid or hydroquinone.
[0023] Furthermore, the catalyst is a platinum complex catalyst;
[0024] The inhibitor is 1-ethynylcyclohexanol;
[0025] The leveling agent is a silicone-based leveling agent.
[0026] The present invention also provides a preparation method of the above-mentioned heat-conducting and puncture-proof silicone material for explosion-proof lithium batteries, which is characterized by including
[0027] Weigh vinyl silicone oil, hydrogen-containing silicone oil, heat-conducting filler, catalyst, inhibitor and leveling agent according to the weight ratio;
[0028] Stir and mix vinyl silicone oil, hydrogen-containing silicone oil, heat-conducting filler and catalyst; then add inhibitor and leveling agent, stir and mix, add to the mold and degas and cure;
[0029] Demold to obtain the heat-conducting and puncture-proof silicone material for explosion-proof lithium batteries.
[0030] Furthermore, the degassing and curing is carried out at 100-130 °C for 5-10 h.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention uses polydopamine derivatives to modify the surface of boron nitride in an oily organic solvent, and further modifies silver nanoparticles to obtain modified boron nitride, which is added as a heat-conducting filler to the silicone material, saving the preparation steps and significantly improving the heat-conducting performance and strength of the silicone material. Specific Embodiments
[0033] In the ranges disclosed in the present invention, the endpoints and any values are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values and individual point values of each range, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention.
[0034] Description of some raw materials used in the embodiments of the present invention:
[0035] Boron nitride, with a size of 3 - 10 μm, purchased from Suzhou Napu Material Technology Co., Ltd.;
[0036] Silicon carbide, 400 mesh, purchased from Dongguan Liaobu Dajiang Abrasive Materials Co., Ltd.;
[0037] Aluminum nitride, with a size of 20 μm, purchased from Zhejiang Manli Nano Technology Co., Ltd.;
[0038] Vinyl silicone oil, purchased from Shenzhen Xinyongsheng New Materials Co., Ltd.;
[0039] Hydrogen-containing silicone oil, model JN - 202, purchased from Shandong Jueneng Chemical Co., Ltd.;
[0040] Hydroxypolyethylene glycol dopamine, with an average molecular weight of 5000, model Tansh, purchased from Guangzhou Tanshui Technology Co., Ltd.;
[0041] Platinum complex catalyst, divinyltetramethyldisiloxane platinum complex, model IOTA 8100, purchased from Anhui Aiyota Silicone Oil Co., Ltd.;
[0042] Silver ammonia solution, with a mass fraction of 5%, purchased from Xiamen Haibiao Technology Co., Ltd., and diluted with ammonia water to the required concentration during use;
[0043] Organosilicon leveling agent, grade BYK - 333, purchased from BYK Chemie GmbH.
[0044] Other raw materials not mentioned are common raw materials in the art and can be directly purchased and used.
[0045] Next, in combination with specific embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0046] Example 1
[0047] A preparation method of a thermally conductive and puncture - resistant silicone material for explosion - proof lithium batteries is as follows:
[0048] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen - containing silicone oil, 0.5 kg of aluminum nitride, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1 - ethynylcyclohexanol, and 0.05 kg of organosilicon leveling agent;
[0049] Step 2: Stir and mix vinyl silicone oil, hydrogen-containing silicone oil, aluminum nitride, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and silicone-based leveling agent and continue to stir and mix for 30 min; then add the mold and keep it degassing and curing at 110°C for 7 h.
[0050] Step 3: Demold to obtain the thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries.
[0051] Example 2
[0052] A preparation method of a thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries is as follows:
[0053] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen-containing silicone oil, 0.5 kg of silicon carbide, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1-ethynylcyclohexanol, and 0.05 kg of silicone-based leveling agent.
[0054] Step 2: Stir and mix vinyl silicone oil, hydrogen-containing silicone oil, silicon carbide, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and silicone-based leveling agent and continue to stir and mix for 30 min; then add the mold and keep it degassing and curing at 110°C for 7 h.
[0055] Step 3: Demold to obtain the thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries.
[0056] Example 3
[0057] A preparation method of a thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries is as follows:
[0058] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen-containing silicone oil, 0.25 kg of boron nitride, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1-ethynylcyclohexanol, and 0.05 kg of silicone-based leveling agent.
[0059] Step 2: Stir and mix vinyl silicone oil, hydrogen-containing silicone oil, boron nitride, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and silicone-based leveling agent and continue to stir and mix for 30 min; then add the mold and keep it degassing and curing at 110°C for 7 h.
[0060] Step 3: Demold to obtain the thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries.
[0061] Examples 4 to 6
[0062] It is basically the same as Example 3, and the only difference is that 0.5 kg of boron nitride is used in Example 4; 1 kg of boron nitride is used in Example 5; 2 kg of boron nitride is used in Example 6.
[0063] Example 7
[0064] A preparation method of a heat-conducting and puncture-proof silicone material for explosion-proof lithium batteries is as follows:
[0065] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen-containing silicone oil, 0.25 kg of modified boron nitride, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1-ethynylcyclohexanol, and 0.05 kg of silicone-based leveling agent;
[0066] Step 2: Stir and mix the vinyl silicone oil, hydrogen-containing silicone oil, modified boron nitride, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and the silicone-based leveling agent and continue to stir and mix for 30 min; then add a mold and keep it at 110 °C for 7 h for degassing and curing;
[0067] Step 3: Demold to obtain a heat-conducting and puncture-proof silicone material for explosion-proof lithium batteries.
[0068] The preparation method of the modified boron nitride is as follows,
[0069] S1: Mix 0.5 kg of boron nitride, 0.02 kg of hydroxy polyethyleneglycol dopamine, and 10 kg of toluene evenly by stirring at 300 rpm for 30 min; then keep stirring at 300 rpm and heat up to 90 °C for reaction for 5 h, and after natural cooling, filter, wash, and dry to obtain an insoluble substance;
[0070] S2: Mix 0.2 kg of the insoluble substance obtained in step S1, 0.02 kg of KH550, and 5 kg of silver ammonia solution (the mass concentration of silver is 0.3%) evenly by stirring at 300 rpm for 30 min; then add 0.02 kg of glucose, keep stirring at 300 rpm and heat up to 80 °C for reaction for 2 h, and after natural cooling, filter, wash, and dry to obtain modified boron nitride.
[0071] Example 8
[0072] A preparation method of a heat-conducting and puncture-proof silicone material for explosion-proof lithium batteries is as follows:
[0073] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen-containing silicone oil, 0.5 kg of modified boron nitride, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1-ethynylcyclohexanol, and 0.05 kg of silicone-based leveling agent;
[0074] Step 2: Stir and mix vinyl silicone oil, hydrogen-containing silicone oil, modified boron nitride, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and silicone-based leveling agent and continue to stir and mix for 30 min; then add the mold and keep it degassing and curing at 110°C for 7 h.
[0075] Step 3: Demold to obtain a thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries.
[0076] The preparation method of the modified boron nitride is the same as that in Example 7.
[0077] Example 9
[0078] A preparation method of a thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries is as follows:
[0079] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen-containing silicone oil, 1 kg of modified boron nitride, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1-ethynylcyclohexanol, and 0.05 kg of silicone-based leveling agent.
[0080] Step 2: Stir and mix vinyl silicone oil, hydrogen-containing silicone oil, modified boron nitride, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and silicone-based leveling agent and continue to stir and mix for 30 min; then add the mold and keep it degassing and curing at 110°C for 7 h.
[0081] Step 3: Demold to obtain a thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries.
[0082] The preparation method of the modified boron nitride is the same as that in Example 7.
[0083] Example 10
[0084] A preparation method of a thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries is as follows:
[0085] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen-containing silicone oil, 2 kg of modified boron nitride, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1-ethynylcyclohexanol, and 0.05 kg of silicone-based leveling agent.
[0086] Step 2: Stir and mix vinyl silicone oil, hydrogen-containing silicone oil, modified boron nitride, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and silicone-based leveling agent and continue to stir and mix for 30 min; then add the mold and keep it degassing and curing at 110°C for 7 h.
[0087] Step 3: Demold to obtain the thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries.
[0088] The preparation method of the modified boron nitride is the same as that in Example 7.
[0089] Comparative Example 1
[0090] A preparation method of a thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries is as follows:
[0091] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen-containing silicone oil, 0.5 kg of modified boron nitride, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1-ethynylcyclohexanol, and 0.05 kg of organosilicon leveling agent;
[0092] Step 2: Stir and mix the vinyl silicone oil, hydrogen-containing silicone oil, modified boron nitride, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and the organosilicon leveling agent and continue to stir and mix for 30 min; then add a mold and keep it at 110°C for 7 h for degassing and curing;
[0093] Step 3: Demold to obtain the thermally conductive and puncture-resistant silicone material for explosion-proof lithium batteries.
[0094] The preparation method of the modified boron nitride is as follows:
[0095] Mix 0.5 kg of boron nitride, 0.02 kg of hydroxy polyethylene glycol dopamine, and 10 kg of toluene evenly by stirring at 300 rpm for 30 min; then keep stirring at 300 rpm and heat up to 90°C for reaction for 5 h, and filter, wash, and dry after natural cooling to obtain the modified boron nitride.
[0096] Comparative Example 2
[0097] A preparation method of a silicone material is as follows:
[0098] Step 1: Weigh 5 kg of vinyl silicone oil, 3 kg of hydrogen-containing silicone oil, 0.05 kg of divinyltetramethyldisiloxane platinum complex, 0.025 kg of 1-ethynylcyclohexanol, and 0.05 kg of organosilicon leveling agent;
[0099] Step 2: Stir and mix the vinyl silicone oil, hydrogen-containing silicone oil, and divinyltetramethyldisiloxane platinum complex at 300 rpm for 30 min; then add 1-ethynylcyclohexanol and the organosilicon leveling agent and continue to stir and mix for 30 min; then add a mold and keep it at 110°C for 7 h for degassing and curing;
[0100] Step 3: Demold to obtain the silicone material.
[0101] Test Example
[0102] The viscosities of the silica gels before degassing and curing in Examples 3 to 6 and Examples 7 to 10 were obtained by rotation using a digital viscometer (NDJ-8S). The results are shown in Table 1.
[0103] Table 1 Viscosity test results of silica gel
[0104]
[0105] In Examples 3 to 6 and Examples 7 to 10, the proportions of the thermal conductive fillers were correspondingly equal. The mass ratios of the thermal conductive fillers (modified boron nitride or boron nitride) to vinyl silicone oil were 5%, 10%, 20% and 40% respectively. It can be seen from Table 1 that the viscosity of Example 6 was as high as 56064 mPa·s, and it was difficult to obtain a silica gel product under this condition. The viscosities of the examples using modified boron nitride were significantly lower than those of the comparative examples under the same mass ratio. It can be seen that by using polydopamine derivatives to modify the surface of boron nitride in an oily organic solvent and further modifying silver nanoparticles, modified boron nitride was obtained, which had better compatibility in the silica gel system than ordinary boron nitride. The improvement of thermal conductivity often depends on the proportion of the thermal conductive filler, and the enhancement of compatibility is conducive to increasing the proportion of the thermal conductive filler, thereby improving the thermal conductivity of the silica gel material.
[0106] Using a thermal conductivity tester, referring to ASTM D5470-2017 "Standard Test Method for Thermal Transmission Properties of Thermal Insulating Materials", the thermal conductivity (unit: W / m·K) was detected and the results were recorded. The results are shown in Table 2.
[0107] Table 2 Thermal conductivity test results
[0108] Thermal conductivity (W / m·K) Example 7 0.81 Example 8 1.24 Example 9 1.82 Example 10 2.53 Comparative Example 1 0.73 Comparative Example 2 0.18
[0109] It can be seen from the test results of Examples 7 to 10 in Table 2 that as the proportion of modified boron nitride increased, the thermal conductivity increased significantly, showing a significant improvement compared to ordinary silica gel (Comparative Example 2). From the thermal conductivity results of Example 7 (mass proportion of modified boron nitride 5%) and Comparative Example 1 (mass proportion of silver-free modified boron nitride 10%), it can be seen that modifying silver nanoparticles further improved the thermal conductivity, and better performance could be achieved even at a low addition amount. This is due to the good dispersion performance of modified boron nitride in the silica gel system, as well as the good thermal conductivity of silver particles and the formation of good thermal conduction channels by the boron nitride matrix in the silica gel.
[0110] Using a material testing machine, the tensile strength of the thermal conductive silicone sheet for testing was detected according to the tensile test method for vulcanized rubber and thermoplastic elastomers ASTM-D412; referring to the standard test method for the tear strength of conventional vulcanized rubber and thermoplastic elastomers ASTM D624, the tear strength of the thermal conductive silicone sheet for testing was detected in a non-notch cutting manner, and the results are shown in Table 3.
[0111] Table 3 Tensile and tear strength test results
[0112] Tensile strength (MPa) Tear strength (N / mm) Example 7 0.53 15.3 Example 8 0.55 15.8 Example 9 0.54 14.3 Example 10 0.49 13.2 Comparative Example 1 0.51 13.9
[0113] From the test results of Examples 7 to 10 in Table 3, it can be seen that as the proportion of modified boron nitride increases, the tensile strength and tear strength first increase and then decrease. The strength of Example 10 (the mass proportion of modified boron nitride is 40%) decreases significantly, but the relative proportion 1 does not decrease significantly. These results indicate that the silicone materials prepared in Examples 7 to 10 of the present invention have good mechanical properties.
[0114] Finally, it should be noted that the above are only the preferred embodiments of the present invention and are not used to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions recorded in the foregoing embodiments or perform equivalent replacements for some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A thermally conductive and puncture-proof silicone material for explosion-proof lithium batteries, characterized in that: In parts by weight, 50-100 parts of vinyl silicone oil; 30-60 parts of hydrogen-containing silicone oil; 2-20 parts of thermal conductive filler; 0.5-1 part of catalyst; 0.2-0.5 part of inhibitor; 0.5-2 parts of leveling agent; The thermally conductive filler is at least one of aluminum nitride, silicon carbide, boron nitride or modified boron nitride.
2. The heat-conductive and puncture-proof silicone material for explosion-proof lithium batteries according to claim 1, characterized in that: The preparation method of the modified boron nitride is: dispersing boron nitride and polydopamine derivatives in an oily organic solvent and then reacting and collecting insoluble matter; The insoluble matter and the silane coupling agent are dispersed in a silver ammonia solution, and then a reducing agent is added to react to obtain modified boron nitride.
3. The heat-conductive and puncture-proof silicone material for explosion-proof lithium batteries according to claim 2, characterized in that: The mass ratio of the boron nitride, the polydopamine derivative and the oily organic solvent is 1-5:0.2-1:50-100; The oily organic solvent is toluene or xylene.
4. The heat-conductive and puncture-proof silicone material for explosion-proof lithium batteries according to claim 2, characterized in that: The polydopamine derivative is hydroxypolyethylene glycol dopamine.
5. The heat-conductive and puncture-proof silicone material for explosion-proof lithium batteries according to claim 2, characterized in that: The mass ratio of the insoluble matter, the silane coupling agent and the silver ammonia solution is 1-5: 0.1-0.5: 20-50; The silane coupling agent is at least one of KH550, KH560 or KH570.
6. The heat-conductive and puncture-proof silicone material for explosion-proof lithium batteries according to claim 2, characterized in that: The mass concentration of silver in the silver ammonia solution is 0.1-0.5%.
7. The heat-conductive and puncture-proof silicone material for explosion-proof lithium batteries according to any one of claims 2 to 6, characterized in that: The mass ratio of reducing agent to insoluble matter is 0.05-0.2:1; The reducing agent is at least one of glucose, ascorbic acid or hydroquinone.
8. The heat-conductive and puncture-proof silicone material for explosion-proof lithium batteries according to claim 1, characterized in that: The catalyst is a platinum complex catalyst; The inhibitor is 1-ethynylcyclohexanol; The leveling agent is a silicone leveling agent.
9. A method for preparing a thermally conductive and puncture-resistant silica gel material for explosion-proof lithium batteries according to any one of claims 1 to 8, characterized in that: include, Weigh vinyl silicone oil, hydrogen-containing silicone oil, thermal conductive filler, catalyst, inhibitor and leveling agent according to weight ratio; Vinyl silicone oil, hydrogenated silicone oil, thermal conductive filler and catalyst are stirred and mixed; then inhibitor and leveling agent are stirred and mixed, added into the mold and degassed and cured; The heat-conductive and puncture-proof silicone material for explosion-proof lithium batteries is obtained by demoulding.
10. The method for preparing the thermally conductive and puncture-resistant silica gel material for explosion-proof lithium batteries according to claim 9, characterized in that: The degassing and curing is maintained at 100-130° C. for 5-10 hours.
Citation Information
Patent Citations
Heat-conducting silica gel sheet applied to new energy automobile and preparation method of heat-conducting silica gel sheet
CN115286832A